Optimizing Irrigation and Young Tree Management - Davie Kadyampakeni; Sandra Guzman (EDIS, 2021)
Young citrus trees require optimal irrigation management for vigorous vegetative growth, leaf flushing, and establishment of a dense canopy. Poor irrigation practices, such as infrequent irrigation or irrigating without using irrigation scheduling tools, could be costly. Besides excessive loss of water and nutrients, the growth of young trees might be impacted by an excess or deficit of water. Crop water stress in young trees directly affects yield and fruit quality. This new 2-page publication of the UF/IFAS Department of Soil and Water Sciences, written by Davie Kadyampakeni and Sandra Guzmán, covers some strategies for optimizing young tree care and irrigation management to in turn optimize grove efficiency and productivity. https://edis.ifas.ufl.edu/ss701